Pengambangan Perangkat Pembelajaran Berbasis Pendekatan Saintifik Materi Pembelahan Sel Kelas XII SMA - Hamka Lodang; Rahmat Baharuddin; Nani Kurnia; Sitti Saenab (JURNAL NALAR PENDIDIKAN, 2022)
This research and development aims to produce learning tools in the form of handouts and Student Worksheets (LKPD) based on a scientific approach to cell division material for class XII SMA that are valid and practical, using the ADDIE development model which consists of five stages, namely analysis (analyze), design, development, implementation, and evaluation. The research location is at SMAN 1 Wonomulyo, Polewali Mandar, West Sulawesi. The research subjects were Biology teachers and class XII students of SMA 1 Wonomulyo. The assessment of the validity of the handouts and worksheets was carried out by two expert validators using a validation sheet. The practicality of the handouts and LKPD were assessed based on the responses of two teachers and 31 students using a questionnaire. The results showed that the average score of the total validity of the handouts and LKPD were 3.50 and 3.53, respectively, with a very valid category. The value of the practicality of the handouts based on the responses of teachers and students are 95.00% and 91.45%, respectively, in the very practical category. The practical value of the LKPD based on the responses of teachers and students is 93.75% and 91.13%, respectively, in the very practical category. It was concluded that the handouts and worksheets based on the scientific approach that were developed were stated to be very valid and very practical.